MAIN QUALITIES AND CHARACTERISTICS OF PEDAGOGICAL ABILITY (Conferencea, 2022)
This article provides full information about the main qualities of teachers in the formation of pedagogical skills, the characteristics of the system of pedagogical skills of teachers.